Českoslovanská strana sociálnědemokratická a antisemitismus (1889-1899) - Soukupová, Blanka (Lidé města, 2000)
Czech historiography and ethnography have not yet fully realized how the atmosphere in the Czech society was pushed forward by the Social Democrat struggle against anti-Semitism. After its reunification, embracing both ideology and organization, in 1889 the party opened a public space which was exploited in varying degree by the masses of its members and followers who were skillfully gained for the idea of internationalism. The paper analyzed the causes (functions) of the Social Democrat struggle against anti-Semitism, its content, means as well as the party's place in the „anti-anti-Semite" political camp which was in the making; this involved a reaction to the transition of anti-Semitism to an institutional framework. At the same time, it tried to refute some mistaken ideas, so far enormously popular both in the Czech historical consciousness and professional literature (such as the image of university teacher T. G. Masaryk as an almost lonely opponent of the ritual murder superstition during the Hilsner affair). However, within its ideological and political propaganda the Social Democrat Party first manipulated anti-Semitism, using it for criticism of rich and socially influential Jewry. This does not in any way lessen the impact and importance of iits ideological fight, it only clarifies the real substance of the Social Democrat propaganda: a European struggle for a place on the political foreground. Anti-Semitism and struggle against it became one of the most efficient ideological and political instruments of modem political efforts, movements and parties.